2012
DOI: 10.1016/s1734-1140(12)70928-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress- and antidepressant treatment-induced modifications of 5-HT7 receptor functions in the rat brain

Abstract: Abstract:This paper summarizes a series of electrophysiological studies aimed at finding the effects of the activation of 5-HT 7 receptors on neuronal excitability as well as on excitatory and inhibitory synaptic transmission in the hippocampus and in the frontal cortex of the rat. These studies demonstrated that 5-HT 7 receptors play an important role in the modulation of the activity of the hippocampal network by regulating the excitability of pyramidal cells of the CA1 area, as well as via their effect on G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…5-HT 7 receptor blockade has been shown to induce antidepressant-like effects in animal models (reviewed in: Ciranna and Catania 2014 ; Nikiforuk 2015 ). These effects occur faster than those induced by conventional antidepressant drugs (Mnie-Filali et al 2011 ; reviewed in: Tokarski et al 2012a ). We have previously demonstrated that treatment with the selective 5-HT 7 receptor antagonist SB 269970 counteracted repeated restraint stress-induced modifications of glutamatergic transmission and synaptic plasticity in the rat frontal cortex (Tokarski et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…5-HT 7 receptor blockade has been shown to induce antidepressant-like effects in animal models (reviewed in: Ciranna and Catania 2014 ; Nikiforuk 2015 ). These effects occur faster than those induced by conventional antidepressant drugs (Mnie-Filali et al 2011 ; reviewed in: Tokarski et al 2012a ). We have previously demonstrated that treatment with the selective 5-HT 7 receptor antagonist SB 269970 counteracted repeated restraint stress-induced modifications of glutamatergic transmission and synaptic plasticity in the rat frontal cortex (Tokarski et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable body of experimental evidence indicates that the 5-HT 7 receptor may be involved in the etiology of mental illnesses (reviewed in Hedlund, 2009 ; Ciranna and Catania, 2014 ). Also, recent research has suggested that the antagonists of this receptor may constitute a new class of antidepressant drugs with a faster therapeutic action than that of the currently used drugs (Mnie-Filali et al, 2011 ; reviewed in Tokarski et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antagonism of 5-HT7Rs can also reverse 5-HT agonist-induced suppression of glutamate release in the DRN and median raphe nucleus (MRN) (Harsing, 2006 ; Pehrson and Sanchez, 2014 ). It has been suggested that there may be 5-HT7 heteroreceptors involved in the inhibition of glutamate release in glutamatergic cortico-raphe projections (Harsing, 2006 ; Duncan and Congleton, 2010 ), whereas 5-HT7R enhancement of 5-HT release may be due to GABA-glutamatergic-serotonergic interactions in the DRN (Harsing et al, 2004 ; Roberts et al, 2004 ; Tokarski et al, 2012 ). More recently, Tokarski et al ( 2011 ) have suggested that 5-HT7R activation may enhance GABAergic transmission in the hippocampus via presynaptic 5-HT7Rs on excitatory glutamatergic input to GABAergic interneurons or activation of post-synaptic 5-HT7Rs on the GABAergic interneurons themselves.…”
Section: Glutamate and 5-ht7 Receptorsmentioning
confidence: 99%